Language use in the immigration experience : A study on foreign immigrants’ language use in Iceland and how it impacts their experience - Anne Garcia 1997- (2023)
Iceland has witnessed a surge in immigration since the end of the 1990’s, especially after the opening of the EU internal borders and the expansion of the EEA. Iceland is now a place of language heterogeneity, with an increasing number of foreign immigrants with various native languages and a heavy influence from English. The literature provides the context of Iceland as an immigration destination and presents previous research on immigrants’ integration and experience of living abroad through the lens of language use. The following thesis aims to understand the language use of immigrants in Iceland and the different ways their experience of Iceland is impacted by it. This study used semi-structured interviews and questionnaires on language uses and exposure of immigrants in different contexts to elicit answers to the question. Results of this study are in line with previous research that language use has an impact on immigrants’ experience. It also provides insights into Iceland specifically as a language diverse country where language use influences aspects of the immigrants’ experience.